Controversies Incorporated: Accepting Androgyny; Women Composers Today: A Personal View; View from the Industrial North; Performance, Notation, Time - Burrell, Diana; Samuel, Rhian; Wilkins, Margaret Lucy; Wishart, Trevor (Contact: A Journal for Contemporary Music (1971-1990), 1988)